Maternal and perinatal outcomes in pregnant women with confirmed severe and mild COVID-19 at one large maternity hospital in Chile. (12th December 2022) - Haye, Maria Teresa; Cartes, Giorgia; Gutiérrez, Jorge; Ahumada, Paz; Krause, Bernardo; Merialdi, Mario; Gonzalez, Rogelio
Abstract: Objective and methods: We conducted a prospective observational cohort study in 458 pregnant and puerperal women, with confirmed COVID-19 at Hospital San Jose, Santiago, Chile, to determine the impact of COVID-19 on pregnancy and confirm safety and feasibility of a management protocol based on clinical presentation of the disease. Results: 25.5% (117/458) of women were severe and 74.4% (341/458) mild presentation. Three percent (9/341) of mild presentations required a subsequent hospitalization. Overall, 26/458 women (5.6%) were admitted to ICU, and 13/458 (2.8%) required mechanical ventilation. One maternal death occurred at 49-days postpartum. Severe presentation, infection above 24 weeks, and comorbidities were associated with an adverse maternal outcome. Of total deliveries, 16.5% (36/217) were <37 weeks. Perinatal mortality was 6/226 (2.7%), mostly due to the fetal component. Conclusions: A quarter of the women had severe COVID-19 that, combined with occurrence of disease in the second half of pregnancy, resulted in substantial maternal compromise. Perinatal morbidity and mortality in women with severe disease were high and warrant consideration. Outpatient management was safe for mild cases.